2023
DOI: 10.3389/fanim.2023.1097071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fennel (Foeniculum vulgare) seed powder addition during early lactation on performance, milk fatty acid profile, and rumen fermentation parameters of Holstein cows

Abstract: IntroductionAromatic and herbal plants usage as feed additives have become a new tendency in dairy cows’ nutrition to enhance animal performance. This experiment was performed to study the effects of supplementing fennel seed powder (FSP) to diets during early lactation on performance, milk fatty acid (FA) profile, and rumen fermentation of Holstein dairy cows.MethodsTwenty-four primiparous Holstein dairy cows (10 ± 3 d in milk, 30 ± 2.1 Kg of milk/d, 610 ± 31 Kg body weight; mean ± SE) were balanced for actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…In line with the present findings, no effect on blood glucose concentrations was observed in previous study (Fahim et al, 2022). On the contrary, the increase in plasma glucose concentration was reported by other studies (Mahmoud et al, 2020;Moosavi-Zadeh et al, 2023). In the present study, the lack of fennel seed effect on blood concentrations of total proteins, albumin, globulin and urea may imply that no alterations in the demand and competition for amino acids occurred and, in turn, shows no challenge to hepatic synthesis of albumin or globulin, required to sustain nutrient transportation and normal immune function (Kargar et al, 2018).…”
Section: Haemato-biochemical Profilecontrasting
confidence: 68%
“…In line with the present findings, no effect on blood glucose concentrations was observed in previous study (Fahim et al, 2022). On the contrary, the increase in plasma glucose concentration was reported by other studies (Mahmoud et al, 2020;Moosavi-Zadeh et al, 2023). In the present study, the lack of fennel seed effect on blood concentrations of total proteins, albumin, globulin and urea may imply that no alterations in the demand and competition for amino acids occurred and, in turn, shows no challenge to hepatic synthesis of albumin or globulin, required to sustain nutrient transportation and normal immune function (Kargar et al, 2018).…”
Section: Haemato-biochemical Profilecontrasting
confidence: 68%
“…Also, Fahim et al [9] indicated that when 75 g of fennel seeds were used as additives in Egyptian buffalo diets, there were no significant differences in milk protein, lactose, and non-fatty solids. In addition to what Moosavi-Zadeh and others [10] found when using fennel seed powder at a concentration of 25 g/day to determine its effect on lactating Holstein cows, there were no significant effects on the milk contents mentioned previously.…”
Section: Milk Componentsmentioning
confidence: 46%
“…The flowers are yellow, tent-shaped, and the fruits are dark gray and smooth, 4-10 mm long, and their shape is cylindrical, pointed, with clear ribs [7,8]. Recent studies also indicated that use of fennel seeds in feeding ruminants had a positive impact on improving milk production and health [9,10]. In light of the increasing prices of feed materials as a result of the decline in general livestock production and its impact on public health, this has led to the need to use local feed additives at reasonable prices.…”
Section: Introductionmentioning
confidence: 99%